Discovering precision health : predict, prevent, and cure to advance health and well-being - Minor, Lloyd B.; Rees, Matthew, 1968- (Hoboken, NJ : Wiley-Blackwell, 2020)
'One of the motivations for launching Precision Health was to confront an uncomfortable reality: in the United States, there's a lot about U.S. health conditions, and our health care system, that's unsatisfactory. To be sure, the United States can be the very best place in the world to obtain the latest, most scientifically advanced treatments for severe diseases for those who have access to these services. But there are dramatic disparities in health, and access to high-quality health care, based on factors such as income and geography. There are also shortcomings embedded in the U.S. health care system, which is one reason why we spend more on health care, on a per-capita basis, than any other country, but our health indicators (such as life expectancy) put us on par with countries that spend less-much less. In this chapter, I examine both U.S. health conditions and U.S. health care, and show how millions of Americans are not seeing the health benefits that are typically associated with living in a high-income country such as the United States'--
Includes bibliographical references and index.
Keywords: Delivery of Health Care; Healthcare Disparities; Health Services Accessibility; Socioeconomic Factors; Precision Medicine; United States